Analysis of N6-methyladenosine reveals a new important mechanism regulating the salt tolerance of sweet sorghum. (March 2021) - Zheng, Hongxiang; Sun, Xi; Li, Jinlu; Song, Yushuang; Song, Jie; Wang, Fang; Liu, Luning; Zhang, Xiansheng; Sui, Na
Highlights: There are considerable differences in the m 6 A modifications of M-81E and Roma. The m 6 A modification is highly complex and dynamic in the regulation of salt stress for sweet sorghum. The m 6 A modification regulates mRNA abundance by regulating the stability of salt-tolerant transcripts. The regulatory of m 6 A activity is limited by the initial m 6 A modification level. Abstract: The N 6 -methyladenosine (m 6 A) modification is the most common internal post-transcriptional modification, with important regulatory effects on RNA export, splicing, stability, and translation. Studies on the m 6 A modifications in plants have focused on Arabidopsis thaliana growth and development. However, A. thaliana is a salt-sensitive and model plant species. Thus, studies aimed at characterizing the role of the m 6 A modification in the salt stress responses of highly salt-tolerant crop species are needed. Sweet sorghum is cultivated as an energy and forage crop, which is highly suitable for growth on saline-alkaline land. Exploring the m 6 A modification in sweet sorghum may be important for elucidating the salt-resistance mechanism of crops. In this study, we mapped the m 6 A modifications in two sorghum genotypes (salt-tolerant M-81E and salt-sensitive Roma) that differ regarding salt tolerance. The m 6 A modification in sweet sorghum under salt stress was drastically altered, especially in Roma, where the m 6 A modification on mRNAs of some salt-resistant related transcripts increased, resulting in enhanced mRNA stability, which in turn was involved in the regulation of salt tolerance in sweet sorghum. Although m 6 A modifications are important for regulating sweet sorghum salt tolerance, the regulatory activity is limited by the initial m 6 A modification level. Additionally, in M-81E and Roma, the differences in the m 6 A modifications were much greater than the differences in gene expression levels and are more sensitive. Our study suggests that the number and extent of m 6 A modifications on the transcripts of salt-resistance genes may be important factors for determining and assessing the salt tolerance of crops.